Assessment of structural materials in compact fusion reactor design - Pettinari, Davide; Meschini , Samuele; Testoni , Raffaella (Frontiers in Nuclear Engineering, 2025)
The development of fusion energy systems demands structural components capable of withstanding extreme operational conditions, including intense neutron fluxes, high thermal and mechanical loads, and stringent requirements on neutron activation. Several structural materials have been proposed, such as nickel-based superalloys, reduced activation ferritic/martensitic steels, oxide-dispersion-strengthened alloys, SiC/SiC ceramic matrix composites, and vanadium-based alloys. While those materials have been extensively analysed for large tokamaks, no comparative studies exist on compact tokamaks. This work addresses this gap by considering an ARC-class tokamak as representative of compact design. The materials are evaluated based on the following criteria: power density deposition, absorption rate, TBR, energy multiplication factor within the breeding blanket, and displacement per atom. Numerical simulations were performed using the OpenMC Monte Carlo particle transport code to evaluate the neutronic behavior and activation characteristics of the selected structural materials. A simplified compact reactor model was developed using Constructive Solid Geometry (CSG) to enable consistent and reproducible comparisons. ODS steels and vanadium-based alloys emerged as the most promising candidates for application in compact, high-temperature fusion devices. ODS steels combine low activation with favorable performance across all evaluated metrics, offering a balanced tritium breeding capability alongside good resistance to radiation damage. Vanadium-based alloys, in turn, exhibit very low hydrogen and helium production, minimal power density deposition, facilitating heat removal from the structural material, and activation levels significantly lower than those of conventional austenitic steels. Across all materials, the simulations predict TBR values in the range of 0.90–1.25, energy multiplication factors of between 1.12 and 1.18, and first structural layer power densities of over 7 MW/m3. In the most favourable cases, the shutdown dose rates fall below natural background levels in less than 50 years.